2022
DOI: 10.1021/acs.analchem.2c03112
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Miniature Mass Spectrometry System for Point-of-Care Analysis of Lipid Isomers Based on Ozone-Induced Dissociation

Abstract: Disorder of lipid homeostasis is closely associated with a variety of diseases. Although mass spectrometry (MS) approaches have been well developed for the characterization of lipids, it still lacks an integrated and compact MS system that is capable of rapid and detailed lipid structural characterization and can be conveniently transferred into different laboratories. In this work, we describe a novel miniature MS system with the capability of both ozone-induced dissociation (OzID) and collision-induced disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…It was found that 2‐HG have a significant increase in glioma tissue with IDH mutation (Figure 6C). Breast tissue samples were also successfully discriminated by detecting changes in phospholipid isomers using the miniature MS with ozone‐induced dissociation (OzID) technique (Liu, Jiao, et al, 2022). Modified from the Mini β with two linear ion traps (LIT1 and LIT2), this miniature mass spectrometer coupled with a miniature ozone generator and used a stainless steel tube to leak ozone into LIT2 for OzID analysis.…”
Section: Clinical Explorations Using Miniature Mass Spectrometersmentioning
confidence: 99%
“…It was found that 2‐HG have a significant increase in glioma tissue with IDH mutation (Figure 6C). Breast tissue samples were also successfully discriminated by detecting changes in phospholipid isomers using the miniature MS with ozone‐induced dissociation (OzID) technique (Liu, Jiao, et al, 2022). Modified from the Mini β with two linear ion traps (LIT1 and LIT2), this miniature mass spectrometer coupled with a miniature ozone generator and used a stainless steel tube to leak ozone into LIT2 for OzID analysis.…”
Section: Clinical Explorations Using Miniature Mass Spectrometersmentioning
confidence: 99%
“…Alternatively, atmospheric pressure chemical ionization after LC separation with subsequent CID yield spectra diagnostic for double bond positions 21 , 22 . Two further methods in this category are direct UV-photodissociation of ionized lipids 23 and the gas-phase ion-molecule reaction with ozone; so-called ozone-induced dissociation (OzID) 24 30 . The latter is particularly suited for de novo identification of previously unknown regio- and stereoisomers at a high dynamic range, because mass selection of the fatty acid species can be performed prior to the ion activation and mass spectral analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The ions are separated by the mass of one oxygen atom (Δ m = 15.9949 Da) and may be assigned as the aldehyde and Criegee ions following decomposition of the primary ozonide (Scheme A); noting the latter species may rearrange to a more stable carboxylic acid or a vinyl hydroperoxide. ,, Interestingly, a range of other abundant product ions are observed and can be assigned by accurate mass to neutral adducts of NO 2 and H 2 O (Figure A). While some level of background water is unavoidable in most mass spectrometers, nitrogen oxides are a specific byproduct of ozone generation and have previously been observed to cluster with some ion types under OzID conditions . For comparison with OzID, 193 nm UVPD of the FA 18:1 n -7, cis [M − H+2Li] + precursor ion on the same instrument yields the predicted pair of product ions at m / z 185.1695 (C 10 H 19 O 2 Li 2 + ) and m / z 209.1695 (C 12 H 19 O 2 Li 2 + ) separated by the mass of two carbon atoms (Δ m = 24.0000 Da, Figure B).…”
Section: Resultsmentioning
confidence: 97%
“…Various human diseases including obesity, diabetes, and Alzheimer’s disease are associated with changes in the cellular lipidome. Cancer is another pathology that is adept at increasing cellular uptake and de novo synthesis of lipids in order to maintain rapid cell proliferation. Consequently, detailed structural characterization of lipids in extracts from cancer cells and tissues is increasingly desirable and requires molecular identification based on lipid class, number of carbons and double bonds (sum composition), relative ( sn -) position of fatty acyl chains in glycerolipids, and the position of functional groups on fatty acyl chains (e.g., unsaturation, methylation, or hydroxylation). Establishing the sites(s) of unsaturation within glycerophospholipids has been a recent focus in cancer lipidomics due to observations of perturbations in desaturation and elongation metabolism , that may potentiate downstream impacts on membrane biophysical properties (e.g., lipid membrane fluidity). , Determining the position(s) of carbon–carbon double bonds is thus central to understanding the variability of human lipid metabolism in health and disease; particularly those pathways involving the expression and activity of the three mammalian desaturase enzymes SCD-1, FADS1, and FADS2. , Notably, changes in the relative abundance of n- 7 and n- 9 double bond isomers in glycerophospholipids have been found to be phenotypic of cancer, while the recent observation of n- 10 double bonds in some cancers is evidence for activation of FADS2 metabolism toward saturated fatty acids; a process first thought to be confined to human skin. , Such discoveries have reinvigorated efforts to develop mass spectrometric techniques capable of assigning double bond position(s) in glycerophospholipids (and other lipid classes).…”
Section: Introductionmentioning
confidence: 99%